Marketing Innovation in E-Commerce: A Study of Its Effects on Customer Retention and Conversion Rates - Ali, Md. Moaz; Mishra, Pranav (Journal of Neonatal Surgery, 2025)
This research delves into the dynamic interplay between marketing innovation and its impact on customer retention and conversion rates within the e-commerce landscape, focusing on the moderating influence of customer satisfaction. The central objective is to offer tangible insights into how marketing innovation strategies shape these pivotal metrics. Employing rigorous quantitative methods, the study meticulously collected data on contemporary marketing innovations in e-commerce. The analytical framework rested on Structural Equation Modelling (SEM) coupled with AMOS. A dataset comprising 275 samples served as the canvas for scrutinizing the nuanced relationships between marketing innovation, customer satisfaction, customer retention, and conversion rates. The Structural Equation Models (SEM) exhibited compelling fits for both Marketing Innovations and Customer Retention (p < 0.05) and Marketing Innovations and Conversion Rates (p < 0.05). Notably, the study uncovered that customer satisfaction is an augmenting force, intensifying these effects. These findings underscore the profound significance of pioneering marketing strategies and customer satisfaction in fortifying overall e-commerce performance. In summation, the research unequivocally validates the substantial role of marketing innovations in significantly enhancing customer retention and conversion rates in e-commerce, with the added amplification through the moderating impact of customer satisfaction.